2011
DOI: 10.4103/0975-7406.90108
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescription patterns at admission into a tertiary level intensive care unit in Northern India

Abstract: Context:An audit of antibiotic prescribing patterns is an important indicator of the quality and standard of clinical practice.Aims:To study the (1) antibiotic prescription and consumption patterns at admission into the intensive care unit (ICU); (2) average costs of antibiotics prescribed; and (3) correlation of antibiotic usage and the costs incurred with age, severity of illness, and diagnosis.Settings and Design:A 13-bedded tertiary level ICU. A prospective, observational audit.Materials and Methods:Two hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
53
4
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 23 publications
16
53
4
2
Order By: Relevance
“…This was comparable with previous studies. 10,11 The reason for more male admissions in our study may be that female patients are reluctant to utilize health care facilities unless they are critically ill. Majority of the patients belonged to 16-30 year age group.…”
Section: Discussionmentioning
confidence: 87%
“…This was comparable with previous studies. 10,11 The reason for more male admissions in our study may be that female patients are reluctant to utilize health care facilities unless they are critically ill. Majority of the patients belonged to 16-30 year age group.…”
Section: Discussionmentioning
confidence: 87%
“…[3][4][5] The most common indication for admission was noncardiac causes and not septicemia, in contrast to other studies. 3,5 The variability in the mean age and indication might be due to presence of separate coronary care unit and other intensive care units like SICU in the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Since patients admitted to the ICU receive multiple drugs, the majority of these drugs are empirically prescribed and mainly based on physician previous experience resulting in the lack of quantitative precision of drugs usage [6]. For example, some European reviews have indicated that over 50% of all neonatal ICU patients received off-label or an unlicensed prescription [7].…”
Section: Introductionmentioning
confidence: 99%